Development of an E-Module Based on 3D Pageflip Professional on the Concept of Vibration and Wave - Melisa Damayanti R. Saleh; Tirtawaty Abdjul; Mohamad Jahja; Mursalin; Ritin Uloli; Asri Arbie (Jurnal Penelitian Pendidikan IPA, 2024)
This e-module based on 3D Pageflip Professional can support and facilitate students in the learning process. This research aims to determine the quality of the E-module based on validity, practicality, and effectiveness. The method used is Research and Development (R & D) with a 4D model. This research was conducted in class VIII, namely Class VIII.1 and Class VIII.2, at SMP Negeri 1 Telaga Jaya. Data collection techniques are carried out through observation, questionnaires, tests, and data analysis using descriptive analysis. The research results show that the validity determined through media expert validation reached 3.69 and material expert 3.77, obtaining valid criteria. The practicality is determined through learning implementation, reaching 90% with very good criteria, and student response reaching 87% with good criteria. The effectiveness is determined through student activity, reaching 89% with good criteria and student learning outcomes with an N-Gain value of 0.8 with high N-Gain criteria. Based on the research results, the E-module based on 3D Pageflip Professional is suitable for use and meets the valid, practical, and effective criteria.